2014
DOI: 10.1016/j.egypro.2014.10.338
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of an Ejector Cooling System Operating with Refrigerant Blends 410A and 507

Abstract: The effect of refrigerant blends 410A and 507 on the operation of an ejector cooling system -ECS-is theoretically studied with the aid of a validated multi-geometry ejector mathematical model. For a system cooling capacity of 1 kW, a set of possible design conditions were obtained by means of a parametric study varying the generator, condenser and evaporator temperatures from 50ºC to 70ºC; 30ºC to 40ºC and 5ºC to 15ºC. The ejector's lower U and values are obtained when R410A is employed, meaning higher primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…Further research should be considered for potential substitutes: for example R1234yf [229] can be a valuable for R134a and has already been investigated for ejector expansion refrigeration system [20, 230-232] and other refrigeration systems [323][324][325][326]. Future studies should also consider refrigerant blends [233].…”
Section: Working Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research should be considered for potential substitutes: for example R1234yf [229] can be a valuable for R134a and has already been investigated for ejector expansion refrigeration system [20, 230-232] and other refrigeration systems [323][324][325][326]. Future studies should also consider refrigerant blends [233].…”
Section: Working Fluidsmentioning
confidence: 99%
“…Due to the limitations in existing working fluids, there is increasing research about potential substitutes (i.e. R1234yf [229] as potential sostitute for R134a [20,[230][231][232]) and refrigerant blends, e.g., Hernandez et al [233] studied blends of 410A and 507. The results indicated that for a certain range of generator temperatures, the refrigerant blend has higher performance if compared with either of the individual refrigerants.…”
Section: Working Fluids In Ejector Refrigerationmentioning
confidence: 99%
“…To make the saving costs not depend on the plant size, the total costs are divided by the heat load: in this way, once obtained the specific savings, they have a more general meaning and are not related to a specific size. The total specific costs per unit of cooling load tc (k€ kW −1 ) can be therefore expressed by Equation (15), in which Y is the fraction of the total lifetime period when the waste heat source is available, as for Equation (16).…”
Section: Total Costs Analysis For Vcc Integrated Usermentioning
confidence: 99%
“…= . (16) Finally, Equation 17provides the specific cost savings with respect to a simple configuration in which the WHRHEC is not considered and only the VCC plant fulfills the cooling load requirements (XWHR = 0): Figure 10a shows the cost savings Δtc as a function of the total lifetime of the combined system for different values of the parameter XWHR. The fraction of the waste heat availability is fixed at 80%, whereas the Italian cost of the electric energy [44] and a SCOP value of 2.5 are considered.…”
Section: Total Costs Analysis For Vcc Integrated Usermentioning
confidence: 99%
“…Hernandez et al [293] revisited the effect of refrigerants, given the operating conditions. Thermodynamic simulation cases for ERS cooling applications comparing R410A and R507 in critical operation were conducted and found by the authors to be suitable options for T g = 50-70 • C, T c = 30-40 • C and T e = 5-15 • C.…”
Section: Conventional Ers Theoretical Studiesmentioning
confidence: 99%